Data validation of gravity field and satellite data using correlation and coherence method - rina dwi indriana; M. Irham Nurwidyanto; Laode M. Sabri (Journal of Physics and Its Applications, 2020)
Satellite data is frequently used as an initial study of a research area for its easy to access feature as well as its improving quality. One of the available satellite data is geopotential data. Satellite data is commonly used to be correlated to the topography data. In this research, satellite data is used as the database of validation in a research area. Valid measuring data is highly required, so that the qualified data is obtained for further process. To identify the validity, additional other QC is required than the existing QC which in 1D. The validation method which applied are correlation and coherence method. The distribution of correlation and coherence values show  asimilirity or compatibility of field data with satellite data. The correlation method was calculate in 2D and the coherence in 1D. Correlation calculation of field data produces high correlation and coherence value to satellite data as much as 0.7 to 0.95 so that it could be identified that acquisition and data processing have been carried out correctly.